Employment relations in the UK civil service. Issue 6 (7th September 2015) - Hodder, Andy
Abstract : Purpose: – The purpose of this paper is to bring together two separate strands of the literature (politics and industrial relations) on civil service management and reform to enable consideration of the industrial relations implications of these changes. Design/methodology/approach: – This paper is conceptual and has no empirical base. The paper is a general review of existing literature on the subject. Findings: – The paper identifies the importance of historical legacy in both management and union behaviour in the civil service. By revisiting earlier civil service reforms, the reader is able to gain an understanding of the rationale for much of the current restructuring of the civil service. Additionally, any discussion of trade union behaviour should be located in the context of union tradition and evolution. Research limitations/implications: – In being a general review, the paper does not report empirical evidence but instead provides the background for future research into civil service industrial relations and management. Originality/value: – This paper is the first to provide a systematic review of management restructuring in the civil service whilst at the same time considering union responses. As such, the paper is of interest to academics and practitioners in the areas of both management and politics.